(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the level of contamination of some microbial agents in milk and dairy products for children under 36 months. Subjects and methods: Cross-sectional descriptive study, sampling and testing 4 common microbiological criteria of 1,500 samples of milk and dairy products circulating in 6 major cities/ provinces. The results were compared with Decision No. 46/2007/QD-BYT, 19/12/2007 of the Minister of Health. ResultS: Milk and dairy products for children under 36 months with the greatest risk of microbial contamination are dairy fats. The most commonly infected organism is Listeria monocytogenes. E.coli: 13.33% of liquid cream samples; 11.11% of avocado samples exceeded the limit. Staphylococus aureus: 12.22% Cream powder samples; 5.00% of the skimmed milk powder samples exceeded the permissible limit. Salmonella: 6.33% of cheese samples, 8.33% of liquid Cream samples; 8.88% of avocado samples, 7.77% of fat samples exceeded the allowable limit. Listeria monocytogenes: 5.00% whey powder sample, 5.00% milk concentrate sample, 3.67% cheese sample, 6.67% butter sample, 10.00% fat sample and 6.00% milk product sample fermentation beyond the allowable limit. Conclusion: Contamination of E.coli, Staphylococus aureus, Salmonella and Listeria monocytogenes still occurs in some milk and dairy products intended for children under 36 months of age, posing a risk of food poisoning for children.